2012
DOI: 10.5897/ajb11.2117
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt removal from wastewater using pine sawdust

Abstract: Agricultural wastes can cause environmental problems if not well managed, but there is a lot of potential to use these wastes as raw material in other processes. In this investigation, pine sawdust was evaluated as an adsorbent in the treatment of wastewater containing cobalt ions. A two-level threefactor full-factorial experimental design with centre points was used to study the interactive effect of the operating parameters in order to achieve the best conditions for the batch adsorption of cobalt ions. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These measurements confirmed the presence of BOF slag powder on the surface of MSSB (Figure 3a). The base morphology of MSSB showed porous linked-fibrous shape, which is similar to the morphology of pine sawdust [33]. The EDS spectra showed that MSSB includes Fe, Ca, Al, Mg, Mn, C, and O (Figure 3c); most of the ions (Fe, Ca, Al, Mg, and Mn) in MSSB seemed to derive from BOF slag powder components, and most C ions seemed to derive from pine sawdust.…”
Section: Physicochemical Properties Of Mssbmentioning
confidence: 65%
See 1 more Smart Citation
“…These measurements confirmed the presence of BOF slag powder on the surface of MSSB (Figure 3a). The base morphology of MSSB showed porous linked-fibrous shape, which is similar to the morphology of pine sawdust [33]. The EDS spectra showed that MSSB includes Fe, Ca, Al, Mg, Mn, C, and O (Figure 3c); most of the ions (Fe, Ca, Al, Mg, and Mn) in MSSB seemed to derive from BOF slag powder components, and most C ions seemed to derive from pine sawdust.…”
Section: Physicochemical Properties Of Mssbmentioning
confidence: 65%
“…Rice hull Fe(C5H7O2)3 11.6-14.3 [20] Red cedar (Thuja plicata) FeCl3•6H2O/FeSO4•7H2O 10-25 [33] Spent coffee ground FeCl3 3.89-8.08 [34] Long-thorn kiawe (Prosopis juliflora) Ni(NO3)2 0.087 [35] Pine tree sawdust BOF slag 2.3 This study…”
Section: Base Materials Additional Components Saturation Magnetic Moment [Emu/g] Referencementioning
confidence: 81%